Conservation Challenges and Emerging Trends of Digital Preservation for UNESCO Architectural Heritage, Pakistan - Asma Khalid (Conservation, 2021)
Recent worldwide initiatives at world heritage forums, especially UNESCO, have increased the importance of architectural heritage. Architectural heritage includes built structures that are of outstanding value of natural and cultural identity and require conservation, preservation, presentation and transmission to the future generations. In this regard, UNESCO has enlisted six World Heritage Sites in Pakistan that need to be preserved. Moreover, the heritage sites are undergoing theft, vandalism, natural decay and other socio-cultural harms. One of the state-of-the-art methodologies is the digital preservation of the historic sites. Amongst the various available computer technologies, photogrammetry is the quickest and most cost-effective method that can be used for digital preservation. The research will focus on the digital preservation of UNESCO World Heritage Sites, which is an emerging trend in an architectural context. Developing countries have limited funds and resources and most historic sites are being neglected by the lack of financial resources. The paper suggests digital preservation as an emerging solution, identifies its challenges and suggests photogrammetry as a cost-effective solution to six UNESCO enlisted historic sites of Pakistan. It also suggests that once digitally recorded, information of historic sites can also be used in diverse applications to generate further finances.